MOLECULAR EVIDENCES OF MUTATION-DRIFT EQUILIBRIUM BY MICROSATELLITE MARKERS IN FOUR MEAT PRODUCER BOVINE BREEDS IN BRAZIL - Ednaldo da Silva Filho; Juliana Simão Nina de Azevedo; Luiz Fernando de Souza Rodrigues; Luiz Marcelo de Lima Pinheiro; Marcia Rocha DeRosia; Taianara Tocantins Gomes Almeida; Frederico Ozanan Barros Monteiro; José Elivalto Guimarães Campelo6. (Journal of Animal and Plant Sciences, 2014)
This study aimed to assess possible deviations in mutation-drift equilibrium in bovine breeds. A total of 178 blood samples were collected from Curraleiro Pé-Duro, Tabapuã, Guzerat and Senepol breeds for DNA extraction and genotypic analysis by eleven microsatellite markers. The deviation loci number to mutation-drift equilibrium was 1 according to allele infinity model (IAM) and 2 by the stepwise mutation model (SMM) for Curraleiro Pé-Duro breed. For Tabapuã breed, there were 5 loci by IAM, and 3 loci by SMM. Although no locus was found by IAM for Guzerat breed, 2 loci were found by SMM. 3 loci by IAM and 2 by SMM were found in Senepol breed. Sign test showed deviation of the number of loci with Heterozygosity excess applying IAM only in Tabapuã breed. In Wilcoxon breed sign test showed deviation of the number of loci with heterozygosity excess in IAM only on Curraleiro Pé-Duro, Tabapuã and Senepol breeds. Overall, the results showed presence of mutation-drift equilibrium. No potential bottleneck effect was detected by mode-shift allele distributions, therefore all breeds were in normal L-shaped. All breeds have shown evidences of mutation-drift equilibrium due more to high loci number of heterozygosity excess than deficiency of heterozygosity.
Keywords: Meat cattle; IAM; SMM; Livestock production; Heterozygosity excess